Eksperimentasi Penerapan Model Pembelajaran the Power of Two Ditinjau dari Kemampuan Berpikir Kritis dalam Pembelajaran Matematika - Lalu Wirajaya (FONDATIA, 2019)
Classroom Action Research applied to Grade VIII students of SMPN 1 Sakra, conducted on the basis of the low level of achievement of the Year-End Achievement Test in Mathematics at the 2017.2018 Academic Year, compared to the average achievement of 2017 Semester Final Assessment / 2018. This study was designed with the Kemmis Action model research procedure, with 2 cycles of action in two meetings. In the description of the results of the research cycle I, and II, there was an increase in the process and results of learning Mathematics with the implementation of the learning model the power of two. In the first cycle, the average score of students' knowledge was 53.67, in the second cycle there was an increase of 73.67, the results of observations of learning activities of students and teachers in cycle I 3, 50 and 2.71 and increased again in cycle II to 4 , 36 and 3.14 with the Good category.